The efficacy of crizotinib in patients with ALK-positive nonsmall cell lung cancer. (June 2015) - Pender, Alexandra; Popat, Sanjay
Molecular profiling of nonsmall cell lung cancer (NSCLC) contributes to better understanding the different molecular subtypes of this heterogeneous group of diseases. The discovery of oncogenic ALK rearrangements in NSCLC and the subsequent success in their therapeutic targeting with crizotinib reinforces the benefits of a precision approach to systemic anticancer therapy. In addition, the rapid development of crizotinib from first discovery thorough accelerated US Food and Drug Administration approval, and late stage confirmatory clinical trials, exemplifies the success of the drug development strategy of close collaboration between clinicians, industry and regulatory authorities. In this review we describe the identification of ALK rearranged NSCLC, clinical characteristics of such patients, and clinical outcomes when treated with crizotinib.